Optimal design of Multiresonant Layered Acoustic Metamaterials (MLAM) via a homogenization approach - Sal-Anglada, G.; Yago, D.; Cante, J.; Oliver, J.; Roca, D. (Engineering structures, 2023)
Broadband sound attenuation at low frequency ranges (below 500 Hz) has been a challenge in the acoustics field which cannot be solved, via conventional materials, unless impractical amounts of mass are employed. Multiresonant Layered Acoustic Metamaterials (MLAM) offer exceptional attenuating properties at lower frequencies, through novel coupled resonances mechanisms, in a layered configuration that make them amenable for large-scale manufacturing. To show the potential capabilities of MLAM, a novel computational design strategy has been developed to optimize the metamaterials’ performance in terms of their Sound Transmission Loss (STL). First, a multiscale homogenization framework specifically derived for MLAM allows an accurate and extremely fast evaluation of their STL response to normal-incidence acoustic waves in the frequency range of interest. Then, the MLAM design is parameterized into a set of relevant geometric features, which are optimized by means of an optimization scheme based on standard genetic algorithms combined with the homogenization model. The results demonstrate how this design strategy is a powerful tool to obtain optimal MLAM panel designs subject to constraints imposed by the application, for instance, in terms of weight or thickness of the panel, or the manufacturing process (e.g. geometric tolerances). •Multiresonant Layered Acoustic Metamaterial (MLAM) is designed for low-frequency STL.•Optimal MLAM improves STL by 20 dB from 100 to 500 Hz compared to wall of same mass.•MLAM structure, design and materials are amenable for large-scale manufacturing.•Layer-by-layer homogenization model is proposed to derive MLAM effective properties.•Two-step parametric optimization strategy using genetic algorithms is proposed.